Two-Dimensional Transition Metal Dichalcogenides: Synthesis, Biomedical Applications and Biosafety Evaluation - Zhou, Xiaofei; Sun, Hainan; Bai, Xue (Frontiers in Bioengineering and Biotechnology, 2020)
Recently, two-dimensional transition metal dichalcogenides (2D TMDCs) have drawn certain attentions in many fields. The unique and diversified electronic structure and ultrathin sheet structure of 2D TMDCs offer opportunities for moving ahead of other 2D nanomaterials such as graphene and expanding the wide application of inorganic 2D nanomaterials in many fields. For a better understanding of 2D TMDCs, one needs to know methods for their synthesis and modification, as well as their potential applications and possible biological toxicity. Herein, we summarized the recent research progress of 2D TMDCs with particular focus on their biomedical applications and potential health risks. Firstly, two kinds of synthesis methods of 2D TMDCs, top-down and bottom-up, and methods for their surface functionalization are reviewed. Secondly, the applications of 2D TMDCs in the field of biomedicine, including drug loading, photothermal therapy, biological imaging and biosensor were summarized. After that, we presented the existing researches on biosafety evaluation of 2D TMDCs. At last, we discussed major research gap in current researches and challenges and coping strategies in future studies.